Hands-on math projects with real-life applications - Muschla, Judith A.; Muschla, Gary Robert (San Francisco, CA : Jossey-Bass, 2006)
A collection of sixty hands-on projects designed to help students in grades six through twelve apply math concepts and skills to everyday, real-life problems.
Professional
Professional
Keywords: Mathematics -- Study and teaching; Activity programs in education; Mathematics -- Study and teaching; Creative activities